Solid tumors in Iranian children: A 12 years retrospective cohort study - Zahra Erfani , Ali Amiri, Sareh Alavirad (Drugs and Cell Therapies in Hematology, 2021)
Introduction: This paper presents epidemiological (incidence, survival, and mortality) data on malignant solid tumors in Iranian children. Methods: A retrospective cohort study evaluated solid tumors in children who referred to Cancer Institute of Tehran University of Medical Sciences from April 1988 to March 2000. After excluding adult patients as well as children with leukemias, 365 cases were eligible for the current study. Results: Solid tumors in children were comprised of 1.35% of all malignancies. The prevalence of solid tumors was highest in the age group of 5-9 years (43.84%). The male to female ratio was 1.8:1. The most common childhood solid tumor was lymphoma (40%), while CNS tumors constituted only 4.11% of solid tumors. The frequency of patients in stages of I, II, III and IV was 1.10%, 8.49%, 29.59% and 53.42%, respectively. 32 out of 33 patients experienced atrophy or deformity of limbs after receiving radiotherapy. We did not detect any secondary malignant neoplasms in our patients. We could only obtain survival and mortality information for 135 patients (36.99%). Conclusions: The prevalence of solid tumors in our country was similar to that of other developing countries. A majority of our patients were in advanced-stages of cancer and we could not gather survival and mortality data for more than half of our patients. This paper highlights the importance of cancer registries and recommends a prospective multicenter study for evaluating the epidemiology of childhood solid tumors.